Researches of metrology descriptions of mean measuring of moment inertia rotors electromotors - Васілевський, О. М. (Proceedings of National Aviation University (archive), 2013)
Static metrology descriptions of mean of measuring of moment of inertia of rotors of electro motors are investigational on the basis of got by decomposition in the row of Taylors functions of transformation of analytical expressions, which describe a sensitiveness, nominal function of transformation, functions of coefficients of influence of influencing parameters and speeds of their change, additive and multiplicative errors.